Factors Affecting the Decision to Make a Buying-Selling Transaction in the Central Rubber Market of the Rubber Authority of Thailand - Tengsuwan, Parichat; Wongsaen, Chiraporn; Chansri, Natthavika (Journal of Applied Economics and Management Strategy [eISSN 2985-1408], 2023)
This research aimed to study the factors affecting the decision to make a buying-selling in the provincial central rubber market by the Rubber Authority of Thailand and analyze the component factors of decision making. The data were collected by interviewing users, both buyers and sellers, including those who do not use the provincial central rubber market to study the reasons for not participating. The total number of samples was 150. The collected data were used for descriptive statistical and exploratory component analyses. The results shows that the factor affecting the decision to purchase in this market is the trading facilitation, purchasing, and process price, respectively. The exploratory component analysis result shows that all 18 factors affecting the decision can be grouped into three groups. The first group is related to the purchasing process of the provincial market includes the dealings, transactions, quality control of the product. The second group is related to the cost of transportation. The final group is related to the price and variety of the product. The most contributing factor to the decision not to buying-selling in the provincial central rubber market by the Rubber Authority of Thailand is the strict quality control measures of the product, followed by the difficulty in becoming a member. Therefore, this research has recommendations as follows; there must be an agency responsible for providing knowledge on product quality, and promoting the creation of a provincial central rubber market network to cover the rubber plantation areas to reduce transportation costs and increase the facilitation of trading.